CRIMINAL LEGAL POLICY AND UNCONSTITUTIONALITY ON CONTEMPT OF RULER OR PUBLIC BODY - Winata, Muhammad Reza; Sinaga, Erlina M. C.; Sabila, Sharfina; Yulistyaputri, Rizkisyabana (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
Contempt of ruler or public body are criminal offence which stipulated in article 207 and 208 Penal Code of Indonesia. In practice, there is legal uncertainty because substantially contradict to Constitutional Court Decision No.013-022/PUU-IV/2006 about contempt of President/ Vice President and No. 6/PUU-V/2007 about contempt of Indonesia Government. This paper wants to found criminal legal policy and constitutionality on contempt of ruler or public body. The research method used is juridical normative with regulation, doctrinal, and decision approaches. The result of study shows changes of criminal law policy on contempt of ruler or public body based on comparison of current Penal Code and future Penal Code Draft with changes elements of formulation: (1) suspect; (2) intention; (3) victim; (4) sanction; (5) impact of action, the norms also transform from general offence to complaint offense. Next, analysis to Constitutional Court decisions about contempt of President/Vice President and Indonesia Government which declared null and void, found related legal reasoning: First, violate freedom of expression; Second, violate right to get information; Third, causing legal uncertainty; Fourth, no longer suitable with society development; Fifth, changes in norms on Criminal Code Draft; Sixth; follow previous decision; Seventh, against universal value in international law. Then, the constitutional interpretation methods used in the decisions are: (1) Ethical Interpretation; (2) Historical Interpretation; (3) Futuristic Interpretation; (4) Doctrinal Interpretation. Therefore, according on similar legal reasoning and constitutional interpretation, article 207 and 208 Penal Code also supposed to be stated unconstitutional.